2013
DOI: 10.1371/journal.pone.0081371
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Shu Complex Utilizes Homologous Recombination Machinery for Error-free Lesion Bypass via Physical Interaction with a Rad51 Paralogue

Abstract: DNA-damage tolerance (DDT) is defined as a mechanism by which eukaryotic cells resume DNA synthesis to fill the single-stranded DNA gaps left by replication-blocking lesions. Eukaryotic cells employ two different means of DDT, namely translesion DNA synthesis (TLS) and template switching, both of which are coordinately regulated through sequential ubiquitination of PCNA at the K164 residue. In the budding yeast Saccharomyces cerevisiae, the same PCNA-K164 residue can also be sumoylated, which recruits the Srs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 56 publications
9
35
0
1
Order By: Relevance
“…While our work indicates that the SWS1 family of proteins functions in meiosis, it is clear that these proteins also promote mitotic HR (Shor et al 2005;Mankouri et al 2007;Ball et al 2009;Bernstein et al 2011;Godin et al 2013;Xu et al 2013). Multiple groups including our own have demonstrated that loss of SHU2 confers sensitivity to replication fork-damaging MMS in various budding yeast strains, and consistent with these findings, previous reports have indicated that loss of SWS1 results in a sensitivity to replication fork-blocking agents in both fission yeast and human HeLa cells (Martin et al 2006;Liu et al 2011).…”
Section: Discussionmentioning
confidence: 77%
“…While our work indicates that the SWS1 family of proteins functions in meiosis, it is clear that these proteins also promote mitotic HR (Shor et al 2005;Mankouri et al 2007;Ball et al 2009;Bernstein et al 2011;Godin et al 2013;Xu et al 2013). Multiple groups including our own have demonstrated that loss of SHU2 confers sensitivity to replication fork-damaging MMS in various budding yeast strains, and consistent with these findings, previous reports have indicated that loss of SWS1 results in a sensitivity to replication fork-blocking agents in both fission yeast and human HeLa cells (Martin et al 2006;Liu et al 2011).…”
Section: Discussionmentioning
confidence: 77%
“…A recent study showed that these interactions support collaboration between the Shu complex, Rad55–Rad57, and Rad52 to promote Rad51 presynaptic filament assembly in vitro [49]. Such a role is consistent with the epistatic relationship between mutants of Rad55–Rad57 and the Shu complex [48,50,51]. As Csm2 mutants that affect its interaction with Rad55, but not Psy3 exhibited a null-like phenotype in terms of genotoxic sensitivity and the reduction of Rad51-mediated gene conversion, the Csm2-Rad55 interaction is an important aspect of Shu complex functions [49].…”
Section: The Shu Complex Promotes Rad51 Function In Recombinationamentioning
confidence: 58%
“…mms2 was found to be epistatic to each shu mutation with regard to sensitivity to DNA-damaging agents, indicating that they function in the same pathway, and each shu mutation also shares a synergistic relationship with rev1 and rev3. Recently, the Csm2 subunit of the Shu complex was found to carry out its HR-promoting function by physically interacting with Rad55, which forms a heterodimer with Rad57, and recruiting it to the stalled replication fork to facilitate the formation of the Rad51 filament on ssDNA [75,76]. In addition, key HR genes (RAD51, RAD52, RAD54, RAD55 and RAD57) were shown to be synergistic with a TLS mutant in a manner typical of mutations in the error-free branch of DDT.…”
Section: Error-free Ddt and Hr Coupling Factorsmentioning
confidence: 99%
“…Thirdly, Csm2 and Psy3 of the Shu complex form a sub-complex structurally similar to Rad51 [100,101], and have a type-specific DNA-binding activity [76]. Recently, a physical interaction between Csm2 and Rad55 was found [75,76], pointing to a possibility that the Shu complex carries out its HR-promoting function by recruiting Rad55-Rad57 to the stalled replication fork by its DNA-binding activity, and this also explains its indirect HR-promoting activity. Alternatively, the Shu complex may also have a direct role in promoting HR, through physical interaction of Shu2 with Srs2 [102].…”
Section: The Antagonism Between Hr-promoting and Hr-suppressing Effectsmentioning
confidence: 99%
See 1 more Smart Citation